Factors Impacting Corporate Social Responsibility of Top Firms Listed in India - Behal, Vikas; Kumar Uppal, Rajinder (Indian Journal of Finance, 2023)
Purpose : The present research work examined the sample of Indian firms to determine the factors impacting top organizations’ corporate social responsibility (CSR) across selected industrial sectors. The objective of this study was to find out the significant determinants of CSR disclosure using financial and non-financial variables. Methodology : Data sources used included annual reports, CSR reports, the company website, and other available public sources. Fixed-effect regression was applied to 708 data observations for the period from 2014–2015 to 2019–2020. The study has developed a total of four regression models for individually testing the influence of promoters’ ownership, institutional ownership, company popularity, and innovation on CSR disclosure. Findings : The findings of this study reported that firm size, firm age, and leverage (gearing) are strong determinants that positively influence CSR reporting. Apart from that, ownership of promoters showed a weak negative effect on CSR disclosure of Indian firms, but profitability does not appear to have any impact on CSR score. However, institutional ownership and innovation are not significant determinants of CSR disclosure. Practical Implications : Larger firms are more accountable and hold a prominent place in society and the community as a whole, therefore, they are supposed to disclose greater CSR information. Furthermore, Indian companies with greater promoter ownership stakes make lesser CSR reporting due to lower information asymmetry and agency conflicts. Originality : The present research on factors affecting CSR, which is under-researched in India, has offered an extensive range of variables by developing advanced regression models.